Catalytic Pyrolysis of Fuel Oil Blended Stocks (FOBS) to Hydrogen and Methane Using Mo/ZSM-5 catalyst - Wan Nur Anis Amira Wan Ranizang; Huzaimah Mazlan; Mohd Asmadi Mohammed Yussuf; Mazura Jusoh; Zaki Yamani Zakaria (Chemical Engineering Transactions)
There was an abundance of very poor-quality oil such as fuel oil blended stocks (FOBS) that caused numerous environmental problems. In this study, FOBS conversion to higher value-added products was achieved through catalytic pyrolysis in a pyrolytic reactor system, producing hydrogen (H2)-rich and methane (CH4)-rich gas. The impact of varying weight percentage of molybdate (Mo) on HZSM-5 (1 %, 3 % and 5 %) and ratio of catalyst-to-feedstock (1:5, 1:10 and 1:15) was explored using pyrolysis reactions. The catalyst was synthesized by using the impregnation method and characterized by using XRD, SEM, FTIR and BET. The characterization results showed that catalyst containing 3 % Mo was more dispersed in ZSM-5 particles. The 3Mo/ZSM-5 catalyst exhibited uniform morphology, a large specific surface area, and good pore size distribution, leading to favorable results in H2 and CH4 gas production. Using 3Mo/ZSM-5, the highest H2 yield of 90.68 % was achieved at a catalyst-to-feedstock ratio of 1:10, while the highest CH4 yield of 83.75 % was obtained at a ratio of 1:5.